Evaluating the shear bond strength and remineralization effect of calcium silicate‐based and conventional self‐adhesive resin cements to caries‐affected dentin - Maryam S. Tavangar; Ayda Safarpour; Arefeh Torabi Parizi; Fereshteh Shafiei (Wiley, 2022)
Abstract Objective Given the importance of preserving caries‐affected dentin (CAD) in conservative dentistry, the shear bond strength (SBS) of different resin cements to CAD has been investigated. Here, we aimed to compare the SBS and remineralizing effect of a calcium silicate (TheraCem) and conventional self‐adhesive cement (Panavia SA) on the SBS of CAD. Materials and Methods Forty‐eight extracted third molars (24 sound and 24 CAD) were used. In each group, 12 teeth were prepared for bonding to TheraCem or Panavia SA. After removal of the enamel and caries, resin composite cylinders were luted on the prepared dentin. After 28 days of storage in the artificial saliva, SBS was measured and the failure mode analysis was investigated. The images of fractured sections were analyzed using scanning electron microscopy and energy‐dispersive X‐ray to evaluate the Ca/P weight ratio. Results SBS of CAD and sound dentin was not different when cemented with TheraCem (9.56 ± 4.51 vs. 9.17 ± 2.76, p = .806), but the CAD showed significantly lower SBS to Panavia SA (9.4 ± 2.36 vs. 7.39 ± 2.18, p = .015). The Ca/P ratio in CAD was significantly higher when bonded to both TheraCem and Panavia‐SA than that of the controls (p = .001); however, this ratio was not different for those bonded to TheraCem compared to Panavia SA. Conclusions Based on our results, TheraCem as a calcium silicate cement shows better SBS to attach the restoration to CAD as compared to Panavia SA. Obliteration and mineralization of the dentinal tubules in TheraCem were also higher than in Panavia SA. However, their ability to improve the amount of the Ca/P ratio in CAD was similar.